The fine-tuning of anti-oxidized low-density lipoprotein antibodies in cardiovascular disease and thrombosis - de Carvalho, Jozélio Freire; Sherer, Yaniv; Shoenfeld, Yehuda (Thrombosis and Haemostasis, 2007)
Anti-oxidised low-density lipoprotein (anti-oxLDL) antibodies are a heterogeneous group of autoantibodies including both pathogenic and protective subsets. Whereas in most studies the levels of anti-oxLDL antibodies were associated with enhanced atherosclerosis as evaluated by different methods, immunization with oxLDL leads to elevated levels of anti-oxLDL and protection against atherosclerosis. Anti-oxLDL can also be used for immunomodulation of atherosclerosis (i.e. possible therapeutic use of intravenous immunoglobulin, oral tolerance). More specific autoantibodies out of total anti-oxLDL should be selected, for instance, anti-oxLDL/beta-2-glycoprotein I complex, hence defining the fine-tuning of anti-oxLDL antibodies might detect which autoantibodies are pathogenic and which can be used therapeutically.
Keywords: oxLDL; anti-oxLDL; autoantibodies; cardiovascular diseases; lipoproteins